Efficiency of mild ovarian stimulation with clomiphene on poor ovarian responders during IVFprocedures: a meta-analysis. (September 2016) - Song, Dan; Shi, Yichao; Zhong, Yun; Meng, Qingxia; Hou, Shunyu; Li, Hong
Abstract: Objective: Our study aims to provide evidence for evaluating the efficiency of mild controlled ovarian hyperstimulation (COH) protocol with clomiphene citrate on ovarian stimulation outcome and pregnancy outcome on poor ovarian respond patients undergoing in vitro fertilization treatment. Methods: For the current study, a search was carried out for relevant randomized controlled trials (RCTs). This meta-analysis was performed on both COH and pregnancy outcomes following the mild COH protocols (CC/Gn/GnRH antagonist) and conventional COH protocols (Gn/GnRH agonist). Outcomes in our analysis were measured in terms of odd ratios (ORs) with 95% confidence intervals (CI) using random effect models or fixed effect models. Results: Four RCTs were finally selected to perform this meta-analysis. Our meta-analysis indicated that there was no significant difference for live birth rate (OR: 0.71, 95% CI 0.22–2.29, P = 0.57) and clinical pregnancy rate (OR: 1.11, 95% CI 0.80–1.55, P = 0.52) for these two COH protocols. A significant heterogeneity was found when meta-analysis was performed on outcomes such as oocytes retrieved numbers, endometrium thickness, and the cancelled cycles. Conclusion: This meta-analysis suggested that mild COH protocol with CC may obtain equal pregnancy outcome on POR patients undergoing IVF treatment compared with that of the conventional COH protocol.